New techniques for membrane protein crystallization tested on photosystem II core complex of Pisum sativum - Kutá Smatanová, Ivana; Gavira, José A; Rezácová, Pavlína; Vácha, Frantisek; García-Ruiz, Juan M (Photosynthesis research, 2006)
The crystallization of a given protein is a hard task being even more complicated when the protein shows a hydrophobic behavior. In the case of photosynthetic proteins, the difficulty of the experiments increased due to the high light sensitivity. Aqueous solutions of photosystem II core complex (OEC PSII) of Pisum sativum were screened for crystallization conditions using standard crystallization methods. Crystal improvement was achieved by counter-diffusion technique in single capillaries of 0.2 mm inner diameter with a three-layer configuration. The use of this advanced crystallization technique-for the first time applied to the crystallization of membrane proteins-improves the reproducibility of the experiments allowing the initial crystal characterization, and facilitates the manipulation under light protection.
Keywords: Crystallization; Membrane Proteins; membránové proteiny; Photosystem II Protein Complex; krystalizace; difuze; fotosystém II (proteinový komplex); hrách setý; Diffusion; Pisum sativum